Echocardiographic evaluation of cardiac dyssynchrony for predicting a favourable response to cardiac resynchronisation therapy. (24th November 2004) - Yu, C M; Bax, J J; Monaghan, M; Nihoyannopoulos, P
Abstract : Cardiac resynchronisation therapy (CRT) is an established therapy for patients with heart failure with wide QRS duration. Recent studies observed that assessment of systolic dyssynchrony is an important diagnostic tool as the treatment involves the re-coordination of regional wall contraction within the left ventricle. Therefore, the effectiveness of CRT depends heavily on whether systolic dyssynchrony is present before the treatment. Echocardiography is a useful tool for quantitative measurement of the severity of dyssynchrony in these patients before and after CRT. A number of echocardiographic tools have been developed during the past three years for such purpose, include M mode measurement of septal-to-posterior wall delay, tissue Doppler imaging for septal-to-lateral wall delay, the measurement of standard deviation of peak contraction time over 12 left ventricular segments, delayed longitudinal contraction, and potentially three dimensional echocardiography. This review discusses the potential role of various echocardiographic techniques in the assessment of systolic dyssynchrony and their clinical applications.